Internal corporate governance mechanism: A review - Abdul Wahab, Norwazli; Sapuan, Noraina Mazuin; Abdinazarovich, Omonov Akrom (Penerbit Universiti Malaysia Pahang, 2022)
Corporate governance (CG) is a comprehensive term that incorporates many distinct facets. Because of numerous financial scandals, public knowledge of CG has increased significantly, particularly in emerging countries like Malaysia. The effectiveness of organizations' adherence with CG legislation and standards is still in question, resulting in numerous incidents of accounting fraud. Furthermore, both internally and externally, company performance is contingent on the effectiveness of Corporate Governance procedures. The purpose of this study is to examine the determinants of internal corporate governance mechanisms and the affect towards financial statement fraud. A comprehensive study of the literature on corporate governance mechanism is carried out. Finally, new lines of research are identified for future study.